2019
DOI: 10.18295/squmj.2019.19.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude Towards the Premarital Screening Programme Among High School Students in Muscat, Oman

Abstract: Objectives: This study aimed to explore high school students’ awareness and attitude towards premarital screening (PMS). Methods: This cross-sectional study was conducted in 10 public high schools in Muscat, Oman from May to July 2016. A three-part self-administered questionnaire was used to collect data from grade 12 students. The first part focused on respondents’ sociodemographic characteristics, while the second part dealt with awareness of the national PMS programme and the third part explored attitudes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
15
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 13 publications
10
15
2
2
Order By: Relevance
“…The majority believed that PMS is important (94.3%, n = 150) and agreed to take the test again if given the chance (84.9%, n = 135). This is a similar finding to what had been reported in previous studies in either Oman (Al Kindi et al 2012;Al-Kindi et al 2019) or others Arab countries such as Egypt, Syria, and Saudi Arabia (Al-Kahtani 2000; Eshra et al 1989;Gharaibeh and Mater 2009). In addition, most of the participants reported that they would advise a future spouse to take PMS test before deciding to marry.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The majority believed that PMS is important (94.3%, n = 150) and agreed to take the test again if given the chance (84.9%, n = 135). This is a similar finding to what had been reported in previous studies in either Oman (Al Kindi et al 2012;Al-Kindi et al 2019) or others Arab countries such as Egypt, Syria, and Saudi Arabia (Al-Kahtani 2000; Eshra et al 1989;Gharaibeh and Mater 2009). In addition, most of the participants reported that they would advise a future spouse to take PMS test before deciding to marry.…”
Section: Discussionsupporting
confidence: 88%
“…In general, health workers' advice plays a role in only 20% of participants. This percentage is fairly close to previous result in where healthcare service was a source of information for only 16.8% of participants (Al- Kindi et al 2019). This indicates that the healthcare services are not as efficient as expected in the PMS program and more effort is required in this regard.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A population study conducted in Saudi Arabia showed that 42% of the examined sample recommended the compulsory implementation of PGS. Another study from Saudi Arabia that was done on high school students showed that female subjects were more likely than male ones to support the laws, legislations, and regulations to prevent marriages of people whose PGS tests are positive [27]. There is always an ethical argument regarding reproductive decisions of at-risk individuals for genetic diseases, and it should be left for the individual to choose.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, creating a legal basis on which to prevent marriages may get in conflict with popular traditions and customs. Consequently, massive campaigns and legal support would be required to improve compliance with health-care team recommendations, especially for individuals with a family history of genetic disorders [27]. On the other hand, some couples might decide not to have children if PGS result is positive and prefer to proceed with their proposed marriage.…”
Section: Discussionmentioning
confidence: 99%